2008
DOI: 10.1016/j.acra.2007.12.020
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Susceptibility of Gadolinium Contrast Media on Diffusion-weighted Imaging and the Apparent Diffusion Coefficient

Abstract: Purpose: The development of parallel MRI has resulted in the frequent use of diffusion-weighted imaging (DWI) in clinical medicine, and it usually involves the use of contrast medium. However, the gadolinium (Gd) contrast medium may have some effect on DWI and the apparent diffusion coefficient (ADC). The present study was performed to determine whether the magnetic susceptibility of contrast medium alters the DWI signal and the value of ADC in some imaging techniques. Materials and Methods:Non-fat suppression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 16 publications
0
25
0
Order By: Relevance
“…DW imaging was performed approximately 10 minutes after injection of a gadolinium-based contrast agent during the dynamic contrast-enhanced MR imaging study. While several studies reported negligible effects of contrast agent on ADC measurements (14,(55)(56)(57), there have been conflicting reports on this topic (58,59), and this factor should also be considered when comparing our results with other studies.…”
Section: Intra-and Interobserver Variabilitymentioning
confidence: 47%
“…DW imaging was performed approximately 10 minutes after injection of a gadolinium-based contrast agent during the dynamic contrast-enhanced MR imaging study. While several studies reported negligible effects of contrast agent on ADC measurements (14,(55)(56)(57), there have been conflicting reports on this topic (58,59), and this factor should also be considered when comparing our results with other studies.…”
Section: Intra-and Interobserver Variabilitymentioning
confidence: 47%
“…Most studies have shown that there was not a statistically significant effect of contrast material on the ADC values. 20,21 However, another study published by Firat et al 22 has shown that contrast medium injection had significant and time-dependent effects on ADC values. According to these findings, they have offered the use of DWI only before or late after contrast material injection for quantitative ADC studies.…”
Section: Discussionmentioning
confidence: 96%
“…Detection of a malignant tumour is based on the increase in signal intensity on DWI, and discrimination between benign and malignant tumours is based on the apparent diffusion coefficient (ADC). However, several factors may alter the ADC (7)(8)(9)(10)(11). Iodinated contrast agents are predicted to affect the ADC due to their high viscosity and large molecular size.…”
Section: Introductionmentioning
confidence: 99%